Enhancing auditors' ability to detect fraud: The influence of brainstorming, integrity, and ethical code implementation - Irwansyah, Irwansyah (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
The increasing incidence of fraud, particularly corruption, underscores the crucial role of auditors in effectively detecting fraudulent activities. This study aims to the influence of brainstorming, integrity, and ethics code implementation on auditors' ability to detect fraud within the Financial and Development Supervisory Board (BPKP). The research employed a purposive sampling method, collecting questionnaire data from 156 auditors working at BPKP. The data were analyzed using regression analysis. The results indicate that brainstorming, integrity, and ethics code implementation positively influence auditors' ability to detect fraud. This study offers practical implications by providing valuable insights for BPKP in enhancing the effectiveness of brainstorming sessions, reinforcing integrity standards, and strengthening the enforcement of ethical codes to improve auditors' fraud detection capabilities.